2013
DOI: 10.3390/land2040609
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Land Change Science and Savanna Fire Models in West Africa

Abstract: Abstract:Fire is a key component of many land use systems and a determinant of land change. There is a growing concern that climate change will cause more catastrophic fires, but in many areas the impacts will be mediated by human land use practices. In African savannas, for example, fires are frequent and research finds low inter-annual variability in burned areas in places with highly variable rainfall. This regularity of fire suggests that African regimes are humanized, meaning that they are governed by hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
0
31
1
1
Order By: Relevance
“…Interviews were conducted between September 1999 and May 2000 in the northern part of the study area and in January 2011 in the southern part (Laris 2002(Laris , 2013. All interviews were conducted in the local languages of Bambara and Malinke.…”
Section: Survey and Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews were conducted between September 1999 and May 2000 in the northern part of the study area and in January 2011 in the southern part (Laris 2002(Laris , 2013. All interviews were conducted in the local languages of Bambara and Malinke.…”
Section: Survey and Interviewsmentioning
confidence: 99%
“…Villages were selected in two study areas with different fire regimes (Laris 2013). Men were randomly chosen from a list of all male heads of households provided by village leaders.…”
Section: Survey and Interviewsmentioning
confidence: 99%
“…This suggests a human control on fires that mediates the climatic influences. Other studies found that fires in African savannahs and especially in West Africa have very regular fire regimes in spite of a variable climate (Giglio et al, 2010;Archibald et al, 2010;Laris, 2013). Recent research works based on a global fire database generated from remotely sensed imagery clearly have shown that the savannahs of western and southern Africa were the areas with the least interannual variability in fires, as well as the most frequently and extensively burned (Giglio et al, 2010;Le Page et al, 2010).…”
mentioning
confidence: 98%
“…Several previous studies were performed from mesoscale to local scale with high-resolution multidisciplinary data such as from Laris (2002Laris ( , 2011Laris ( , 2013 and Le Page (2010) on the human role in fire variability. Our study focuses on the regional scale (West Africa), the potential links between climate indexes and burned areas derived from satellite.…”
mentioning
confidence: 99%
“…Yet, clandestine fire use and management continues around the world (Kull 2002;Laris 2013;Seijo 2005;Tacconi and Ruchiat 2006). This paper asks (1) whether or not informal management regimes persist in the state of Georgia (USA) in the form of unauthorized fire-setting and (2) if those practices can inform disturbance-based land management.…”
Section: Introductionmentioning
confidence: 99%